Measuring Quarterly Economic Growth from Outer Space - Beyer, Robert C.M.; Hu, Yingyao; Yao, Jiaxiong (World Bank, Washington, DC, 2022)
This paper presents a novel framework to estimate the elasticity between nighttime lights and quarterly economic activity. The relationship is identified by accounting for varying degrees of measurement errors in nighttime light data across countries. The elasticity is 1.55 for emerging markets and developing economies, with only small deviations across country groups and different model specifications. The paper uses a light-adjusted measure of quarterly economic activity to show that higher levels of development, statistical capacity, and voice and accountability are associated with more precise national accounts data. The elasticity allows quantification of subnational economic impacts. During the COVID-19 pandemic, regions with higher levels of development and population density experienced larger declines in economic activity.